Philanthropy in practice: pragmatism and the impact of philanthropic action - Thümler, Ekkehard (Taylor and Francis, 2017)
Cover -- Title -- Copyright -- Dedication -- Contents -- List of figures -- Acknowledgements -- 1 Introduction: Contemporary Philanthropy and Its Problems -- Part I Theory -- 2 Pragmatism and the Evolution of Intelligent Social Action -- 3 Mapping the Space of Social Problems -- 4 A Contingency Model of Problem-Solving Strategies -- 5 The Role of Niches in Processes of (Social) Innovation -- Part II Case Studies -- 6 The Chance: Opening the Doors to the Labour Market for Disadvantaged Youth -- 7 Foundation Interkultur and the Intercultural Garden Movement: Catalysing Emerging Practice at the Grassroots -- 8 The Nuffield Foundation and the Nuffield Council on Bioethics: Organising the Provision of Non-Partisan Expertise -- 9 The Joseph Rowntree Charitable Trust and the Campaign for Freedom of Information: Campaigning for Access to Files -- Part III Analysis -- 10 From Exploration to Exploitation: The Pragmatic Model of Action in Philanthropic Practice -- 11 Explanations for Social Impact: The Door-Opener Mechanism -- 12 Towards a Model of Philanthropic Niches and Intelligent Niching -- 13 Conclusion and Outlook -- Appendix A: List of Cases -- Appendix B: Interview Schedule -- References -- Index
Keywords: Hochschulschrift; Management; Nonprofit-Organisation; Philanthropie